Strategy for utilizing local wisdom in the development of Blue Economy in marine ecotourism on Gili Genting Island, Sumenep Regency - Moh. Musleh; Deasy Arieffiani (Journal Public Policy, 2026)
The purpose of this study was to analyze and identify how the strategy of utilizing local wisdom in the development of blue economy in marine ecotourism on Gili Genting Island, Sumenep Regency. This research uses descriptive qualitative methods by prioritizing the meaning and actions of the experiences of a group of people and social behavior. Data collection techniques by conducting observations, interviews, and browsing documentation. Key informants namely, the Sumenep Regency Youth Culture and Sports Tourism Office, related village governments, private parties, PokDarwis, and Gili Genting Island community leaders. The data analysis technique uses four steps from Creswell, namely data collection, data reduction, data presentation and conclusion drawing. Based on the previous data collection, the data from interviews, field observations, and documentation review were then compared and compiled to obtain synthesis results between the three and presented thematically. The results show that zero waste management and waste management efforts have been made, however, challenges such as seawater intrusion, plastic waste, coral reef damage, and lack of community involvement still exist. Community empowerment, preservation of local wisdom, and government support are important to create inclusive and sustainable tourism. Marine ecotourism has the potential to improve the local economy through employment and infrastructure investment, with innovation, climate change adaptation, and cooperation between stakeholders, Gili Genting can become a sustainable ecotourism destination that preserves the environment and community welfare.